Praktik Utang piutang Dalam Membangun Rumah dengan Sistem “Titip” Dilihat dari Perspektif Ekonomi Syariah - Muhammad Ngasifudin; Tri Almunawaroh (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
There is one habit which often carried out by Cimucung Village’s pupil in providing aid, namelygiving a money loan called “titip” system. “Titip” is debt system that helps pupil to buy rawmaterials for building houses. Consequently, the debt is paid by similar raw materials to the lender.This system does not always work well because there are several main obstacles, including noofficial debt agreement. This research aims to (1) investigate agreements that are used in “titip”system; (2) analyze the legal basis of dealing with material and it will be paid by using money; (3)analyze the law of materials payable. This research used qualitative method. Techniques ofcollecting data used observation, interview, and documentation. Menawhile, the data analysed byusing descriptive method. Research outcomes showed that the agreement that used in “titip” systemwas al-qardh. While the lender provided material as loan and the borrowers paid by using moneythen the law is permitted. In addition, if the borrower paid more debt and it was not an agreementthen the law is permitted. Furthermore, while the lender provided money as the debt but they askedthe borrower paid with raw materials then the law is permitted. The law is also allowed byobserving agreements that have been agreed before. On the other hand, when the borrower paid thedebt, there will be no dispute over returns with money or raw material.